PENGUJIAN BEBERAPA METODE PEMBUATAN BIOAKTIVATOR GUNA PENINGKATAN KUALITAS PUPUK ORGANIK CAIR - Aminah Sarwa Endah; Aman Suyadi; Gayuh Prasetyo Budi (Universitas Muhammadiyah Purwokerto, 2015)
This research is aimed to find out the method of bio activator process and the best basic material used to produce a good qualified POC. This research was done in integrated laboratory of Muhammadiyah University of Purwokerto from April 2013 to August 2013.This research used A Complete Randomized Design with two factors. The first factor was the three kinds of bio activator like decayed banana leg method (A1), bio activator method of fruit and red onion (A2) and bio activator method of stratified water rice (A3). The second factor was three kids of organic waste as the basic material to make the Liquid Organic Fertilizer such as organic waste (B1) manure (B2). Every treatment was done for three times.The result of the research showed that bio activator, organic waste, and bio activator interaction as well as organic waste in fermentation process did not really affect on the weather variable and the pH of Liquid Organic Fertilizer. The result also showed that LiquidOrganic Fertilizer, based on the standard quality by the minister of agriculture regulation Number.28/Permentan/OT.140/2/2009, contained of total N, total P2O5, total K2O in every treatment, and the content of ratio C/N and organic C did not meet the standard quality by the minister of agriculture regulation Number. 28/Permentan/OT.140/2/2009.